A reformulação parafrástica na fundamentação teórica de trabalhos de conclusão de curso de Letras - Bernadino, Rosângela Alves dos Santos (2009)
In this work, we study the types of paraphrases used by the students of the Language and Literature Course when they reformulate a source text in the theoretical section of the monographs produced as texts for the conclusion of the course. Our main goal is to know how the process of textual reformulation takes place in the production of the monographic gender. From the used theoretical orientation (Fuchs,1982; 1994; Charaudeau and Maingueneau, 2006; Fávero et al, 2007; Hilgert, 1997, 2002, 2006; among others) we have worked with the paraphrase notion as an activity of discoursive reformulation, considering as the basic groundings the situation of communication and the subjects, or the wider context. In a more specific way, we have considered that the paraphrase performs alterations in the formal level, in the semantic level and in the functional level. Besides that, we sought to articulate the practice of paraphrasing to the gender of discourse in which it appears and to the contextual implications involved in the producing of the gender in question, and in doing so we were grounded in Baktin´s (2003) and Maingueneau´s (1998; 2001) postulates. For the analysis of the corpus that consists of 19 monographs, we have used the three categories defined by Hilgert (2002, 2006):expansion, condensation and parallelism as a way of identifying, describing and characterizing the types of paraphrases used by the students who produced the monographs when they take up Travaglia´s (1996) text about the language conceptions. The results show that the use of the paraphrastic parallelism (with 69.45 % in relation to only 18.41% of condensation and 12.13 % of expansion) was the most recurrent in the reformulations performed by the students who produced the monographs and this manifestation was characterized mainly by the lexical-semantic repetition of fragments of the source text. We have concluded that the high incidence of paraphrastic parallelism is an indication that the student does not have a command of the ways of production and circulation of the discoursive genders uttered in the academic-scientific realm